Role of 18F-FDG PET/CT scan and MRI for Predicting Pathological Response to Neoadjuvant Chemotherapy in Breast Cancer Management (Bangladesh Journal of Nuclear Medicine, 2025)
Background: Neoadjuvant chemotherapy is used in breast cancer patients to reduce tumor size and prevent micrometastasis, with accurate assessment through 18F-FDG PET-CT and DCE-MRI providing operation guidelines. Objective: To establish the diagnostic accuracy of 18F-FDG PET-CT scans and MRI compared to pathological response for NAC assessment in BC management. Patients and Methods: This cross-sectional comparative study was conducted at NINMAS, Shahbag, Dhaka, under a Coordinated Research Project (CRP)-E1.30.44 of IAEA. The study spanned from September 2022 to February 2024, examining 17 stage II and stage III BC patients who had received NAC before surgery and had prior 18F-FDG PET-CT and DCE-MRI studies. For therapy response of NAC, 18F-FDG PET-CT and MRI were performed after completion of NAC. Parameters of 18F-FDG PET-CT and MRI were obtained and evaluated by using PET Response Criteria in solid tumors (PERCIST) 1.0 based on SUV normalized by lean body mass (SULpeak) in PET-CT and Response Evaluation Criteria in solid tumors (RECIST) 1.1 based on the longest diameter in MRI of primary tumors and axillary lymph nodes, respectively. Descriptive and analytical analyses were performed to examine 18F-FDG PET-CT and MRI to compare pathological response after surgery, and diagnostic accuracies were compared. Result: The study patients were divided into responder 12 (70.5%) and non-responder five (29.4%) groups according to overall pathological response to NAC after surgery. Both RECIST 1.1 and PERCIST 1.0 with post-surgical pathological response to NAC of BC patients were compared. The sensitivity of PET-CT with pathological response to NAC of the study population was 80%, followed by specificity 100%, positive predictive value (PPV) 100%, and negative predictive value (NPV) 92.31%. The sensitivity of MRI with pathological response to NAC of study patients was 100%, followed by specificity at 83.33%, PPV at 71.43%, and NPV at 100%. The accuracy levels of PET-CT and MRI were 94.12% and 88.24%, respectively. PPV and accuracy compared to RECIST 1.1.; PERCIST 1.0 was more accurate in predicting pathological response to NAC of BC patients. Conclusion: PET-CT accurately predicts pathological response in breast cancer patients following NAC, reducing surgical intervention and chemo radiation burden, thereby reducing the need for chemo radiation.Bangladesh J. Nuclear Med. 28(1): 22-30, 2025